EFEKTIVITAS MANAJEMEN PENGEMBANGAN KOMPETENSI GURU DALAM PENERAPAN KURIKULUM MERDEKA - Adekamisti, Revi; Warsah, Idi; Adisel; Warlizasusi, Jumira (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2024)
Competency-based educational management emphasizes the importance of well-planned and sustainable human resource management to achieve optimal educational goals. This study aims to evaluate the effectiveness of teacher competency development management in the implementation of the Kurikulum Merdeka (Independent Curriculum) based on competency-based educational management theory. The research employs a mixed-methods approach with an evaluative design. The subjects consist of 20 teachers from SD Negeri 01 Bermani Ilir, SD Negeri 19 Kepahiang, SD Negeri 01 Kepahiang, SD Negeri 15 Kepahiang, SMP Negeri 2 Kepahiang, SMP Negeri 1 Kepahiang, and SMP Negeri 2 Tebat Karai. Data were collected through questionnaires, interviews, observations, competency tests, and document analysis, and subsequently analyzed using descriptive statistics and thematic analysis. The results reveal that the effectiveness of teacher competency development management has not yet reached an optimal level. A total of 60% of teachers rated the training management as moderately effective, while 40% considered it less effective. Identified challenges include a lack of practice-based training, limited facilities, and high administrative workloads. Teachers with strong management support showed improvements in understanding and implementing the Kurikulum Merdeka, although maintaining consistency remains a challenge. This study concludes that teacher competency development management needs enhancement through more relevant training, strengthened supervision by school principals, improved access to technology, and more efficient management of administrative workloads. These strategic recommendations are expected to support the successful and optimal implementation of the Kurikulum Merdeka.